Canadian Economists’ Citation and Publication Records - Grubel, Herbert G. (Canadian Journal of Higher Education, 1981)
This paper uses the Social Science Citation Index to count the number of citations received and publications made by all economists teaching at Canadian universities in 1975. It is shown that the top decile of individuals received 72 percent of all citations and 50 percent received none. The University of British Columbia and Simon Fraser Univer- sity departments of economics have the highest and second-highest average citation counts of all Canadian universities, respectively. The age-profile of citations, self-citation propensities and the journals of publication are analysed from a sub-sample of data.